South elevation of the Mandapa of the Suhaveshwar Temple - Temples of India Project Team (Jio Institute, 2024)
This is a view of the south elevation of the mandapa (pillared hall) of the Suhaveshwar Temple. The mandapa has two lateral transepts on the north and south sides. Both the mukhamandapa (front porch) and the mandapa have pyramidical shikharas atop them. The shikhara (superstructure) on the mandapa is of the samvarana (pyramid-shaped) variety. The juncture of the pillars of the mandapa and the shikhara are marked by a protruding chajja (balcony).